FAKTOR-FAKTOR YANG MEPENGARUHI TIONGKOK MEMBENTUK KERJASAMA CHINA-PAKISTAN ECONOMIC CORRIDOR (CPEC) - Daniel S; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research would explain about factors affecting China Formed the China-Pakistan Economic Corridor (CPEC) cooperation. The establishment of this partnership is part of China’s One Belt One Road (OBOR) initiative.The Author uses the perspective of Liberalism, Interdependence Theory, and the analysis system is the nation state.This research uses an explanatory qualitative, the data collection techniques by library research are derived from sources of literature book, published magazine, journals, and scientific articles.The result of this research describe the reason China formed CPEC. Factors affecting China to establish CPEC are to provide transportation access for China to reduce the distance of Chinese energy import and international trade that had to pass through the Strait of Malacca to reach the Arabian Sea. As part of OBOR, CPEC will provide economic opportunities for the western region of China and the South Asia region, especially Pakistan.Key words: CPEC, Pakistan, OBOR, Regional Integration, Foreign Direct Investment, Infrastructure and Energy Development.